ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA KELAS 1 SEKOLAH DASAR - Asty Septiani Asran; Dina Nadira Cahyani; Selvi; Idawati (STKIP Subang, 2026)
Mathematics learning in the early grades of elementary school plays a crucial role in developing students’ foundational numeracy skills. However, many first-grade elementary school students still experience difficulties in learning mathematics, particularly in understanding basic numeracy concepts and simple arithmetic operations. This study aims to analyze in depth the mathematics learning difficulties experienced by first-grade elementary school students and the factors contributing to these difficulties. This research employed a qualitative approach with a descriptive research design. Data were collected through classroom observations during mathematics learning activities and semi-structured interviews with classroom teachers and several students. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that students experience difficulties in recognizing number symbols, understanding number values, and performing simple addition and subtraction operations. In addition, students demonstrate low self-confidence, limited learning motivation, and difficulties in comprehending word problems. The contributing factors to these learning difficulties include differences in students’ initial numeracy abilities, limited use of concrete learning media, and less varied instructional methods. The study concludes that mathematics learning difficulties among first-grade elementary school students are complex and multidimensional, involving cognitive, affective, and pedagogical aspects. Therefore, it is necessary to implement contextual learning strategies, utilize concrete learning media, and apply instructional approaches that are appropriate to the developmental characteristics of early-grade students.